Tinjauan Yuridis Terhadap Tindak Pidana Penyalahgunaan Narkotika Golongan I Bagi Diri Sendiri (Studi Kasus Putusan Nomor 412/Pid.Sus/2024/PN.Mjk) - Anggita Permadi; Sri Astutik; Noenik Soekorini; Vieta Imelda Cornelis (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Drug abuse is a serious legal and social problem in Indonesia. The distribution and consumption of narcotics not only impact public health but also have complex legal implications in the criminal justice system. This study aims to analyze the application of substantive criminal law to the crime of drug abuse class I for oneself and examine the judge's considerations in handing down a verdict in case Number 412/Pid.Sus/2024/PN.Mjk. The research method used is normative legal research with a statutory approach and a case approach. The data used consists of primary data in the form of court decisions and secondary data in the form of laws and regulations, legal literature, and scientific journals. The results of the study indicate that the application of criminal law to drug abuse for oneself still generates debate between a repressive approach through punishment and a rehabilitative approach. In the decisions analyzed, the judges considered juridical, sociological, and philosophical aspects in handing down a verdict against the defendant. This study concludes that the criminal justice system should prioritize a rehabilitation approach for drug abusers who are proven to be victims of dependence in accordance with the provisions of Law Number 35 of 2009 concerning Narcotics.